GREEN HUMAN RESOURCE MANAGEMENT: A COMPARISON OF POLICIES AND PRACTICES IN SOUTH AFRICA AND THAILAND - Putthiwanit, Chutinon; Chidau, Tatenda Lincoln (The journal of contemporary issues in business and government, 2023)
Human resource (HR) in organizations has to keep up with changes, adjust and avoid being complacent by sticking to traditional roles to remain relevant. There is consensus for countries and organizations to be proactive with environmentalism. Green human resource management (GHRM) is a topical agenda amongst human resource management (HRM) researchers and new literature emerging. As a result, the main aim of this study is to explore and compare the policies and practices of GRHM in South Africa and Thailand. This particular study, employed a qualitative approach – systematic review – followed a desktop approach and looked at different literature sources that researchers analyzed, summarized, and draw suppositions about GHRM in South Africa and Thailand. The results show that even though various researchers carried out studies on GHRM, very few focus on South Africa and Thailand. There are also discrepancies between the awareness and implementation. However, various HR practitioners in South Africa have a perception that greening activities should not be the main priority of the HR department but of environmental specialists.